2014
DOI: 10.1136/gutjnl-2014-307023
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir treatment does not eliminate the risk of hepatocellular carcinoma in chronic hepatitis B: limited role for risk scores in Caucasians

Abstract: Cumulative incidence of HCC is low in patients treated with ETV, but ETV does not eliminate the risk of HCC. Discriminatory performance of HCC risk scores was limited, particularly in Caucasians, at baseline and during therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
185
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(208 citation statements)
references
References 13 publications
17
185
1
5
Order By: Relevance
“…Some of these risk factors have been used to construct clinical scoring systems for the prediction of HCC (12)(13)(14)(15). However, HBeAg sero-status and the levels of HBV DNA and ALT are usually changeable during the long-term HBV infection, and differ among the patients infected with different HBV genotypes, which might result in low discriminatory performance in different populations (16)(17)(18)(19)(20)(21). Therefore, more robust biomarkers are needed to improve the prediction power of the current clinical scoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these risk factors have been used to construct clinical scoring systems for the prediction of HCC (12)(13)(14)(15). However, HBeAg sero-status and the levels of HBV DNA and ALT are usually changeable during the long-term HBV infection, and differ among the patients infected with different HBV genotypes, which might result in low discriminatory performance in different populations (16)(17)(18)(19)(20)(21). Therefore, more robust biomarkers are needed to improve the prediction power of the current clinical scoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them, such as GAG-HCC, CU-HCC and REACH-B, have been developed and validated in Asian untreated CHB patients, 25 but they do not seem to offer good predictability in most studies including Caucasian CHB patients. 26,27 A recently developed and validated new score, PAGE-B, offers good predictability for HCC during the first 5 years of entecavir or tenofovir therapy in Caucasian, mostly European, CHB patients and can be easily applied in clinical practice, as it is based on widely available parameters (platelets, age, gender).…”
mentioning
confidence: 99%
“…within the VIRGIL Network, the 5-year cumulative incidence rates of HCC were 2.1 and 10.9 % for non-cirrhotic and cirrhotic patients, respectively [18]. They concluded that the cumulative incidence of HCC is low in patients treated with ETV, but that ETV does not eliminate the risk of HCC.…”
mentioning
confidence: 99%
“…However, this would need much bigger sample sizes in order to have a large enough number of patients left after PSM. Another approach is to compare the observed incidence of HCC in the treated cohort with that projected in untreated cohorts by prediction models such as CU-HCC, GAG-HCC or REACH-B [18]. This should also be carried out cautiously because the application of the models is conditional, for example, other hosts (such as ethnic groups) and viral factors (such as genotype and HBeAg status) which should be taken into consideration.…”
mentioning
confidence: 99%
See 1 more Smart Citation